Global deepwater circulation between 2.4 and 1.7 Ma and its connection to the onset of Northern Hemisphere Glaciation - Du, Jianghui; Huang, BaoQi; Liping Zhou (Paleoceanography, 2016)
We have generated an early Pleistocene benthic isotopic record for the Ocean Drilling Program Site 807 (2804 m) from the western equatorial Pacific. Between 2.4 and 1.7 Ma, the benthic δ13C of this site and a few other deep Pacific sites was consistently higher than the Southern Ocean Site MV0502-4JC (4286 m), pointing to a reversal relative to the current gradient and hence implying a different circulation regime. We reconstructed the deepwater mass distribution of this interval by using a collection of benthic isotope records from 15 Pacific and 10 Atlantic sites and a δ13C-δ18O mixing model. A two-end-member mixing regime between the North Atlantic Deep Water (NADW) and the Antarctic Bottom Water (AABW), with properties very different from today, was identified. The Southern Ocean showed strong signs of stratification and AABW with low benthic δ13C, but high δ18O values reached out to other basins only below ~4000 m. In contrast, NADW ventilated most of the ocean interior, contributing ~70% to the Pacific Deep Water volumetrically. Our model results also reveal a strong remineralization effect at the bottom sites of the Pacific and the Atlantic, suggesting significant accumulation of respired carbon in the bottom water between 2.4 and 1.7 Ma. We propose that such a circulation pattern was initiated by the reversal of salinity gradient between AABW and NADW from 3.0 to 2.4 Ma, possibly linked to Antarctic sea ice expansion and reduced southward heat transport during the onset of Northern Hemisphere Glaciation.
Keywords: 0473 Paleoclimatology and paleoceanography; 4283 Water masses; 4870 Stable isotopes; 4962 Thermohaline; 5416 Glaciation; benthic stable isotopes; deepwater circulation; early Pleistocene; Northern Hemisphere Glaciation